2019
DOI: 10.1007/s42452-019-0227-8
|View full text |Cite
|
Sign up to set email alerts
|

A layered IoT architecture for greenhouse monitoring and remote control

Abstract: Wireless Sensor Networks have been often used in the context of Greenhouse architectures. In this paper, an architecture is proposed for two Greenhouses based on Networked Control Systems. This architecture is IoT-based and built on top of switched Ethernet and Wi-Fi. Some sensors in the proposed architecture require a one-second real-time deadline. Riverbed simulations prove that there is zero packet loss and no over-delayed packets. An important contribution of this work is the design of a channel allocation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(16 citation statements)
references
References 21 publications
0
15
0
1
Order By: Relevance
“…The objective of this study was to build upon existing work on cyber risk standardisation [10], and AI in CPS [11], but with a greater focus on exploring the potential and practical challenges in the use of AI, in the service of improving personal and organisational resilience. The methodology applied in the study follows recommendations in existing studies on adaptive risk models [12]; feedback in IoT systems [13]; in layered IoT architecture [14]; and for optimising decision-making [15]. We identified approaches to model the risk within complex interconnected and coupled systems in cyber-physical environments.…”
Section: Introductionmentioning
confidence: 99%
“…The objective of this study was to build upon existing work on cyber risk standardisation [10], and AI in CPS [11], but with a greater focus on exploring the potential and practical challenges in the use of AI, in the service of improving personal and organisational resilience. The methodology applied in the study follows recommendations in existing studies on adaptive risk models [12]; feedback in IoT systems [13]; in layered IoT architecture [14]; and for optimising decision-making [15]. We identified approaches to model the risk within complex interconnected and coupled systems in cyber-physical environments.…”
Section: Introductionmentioning
confidence: 99%
“…Field monitoring applications are designed to report on different conditions such as soil fertility, temperature, humidity, gas content, air and water pressure, and the presence of disease in crops [22]. The use of IoT sensors and devices has also managed to eliminate the need for manual intervention to some extent, constituting a smart greenhouse design able to monitor and regulate various climatic parameters in accordance with the plants' needs [23].…”
Section: Internet Of Things (Iot)mentioning
confidence: 99%
“…IoT base Precision farming consist of multiple monitoring and controlling applications such as climate conditions monitoring, soil patterns monitoring, pest and crop disease monitoring, irrigation, determine optimal time to plant and harvest and tracking/ tracing. Ibrahim et al [57] reported that the cultivation of greenhouse is more intense, therefore in terms of controlling and monitoring it requires high precision. To monitor environmental or weather conditions there have been several studies on the applications of WSN's in greenhouse.…”
Section: Internet Of Things (Iot) In Agriculture Formentioning
confidence: 99%